Problematic mobile phone use and time management disposition in Chinese college students: the chain mediating role of sleep quality and cognitive flexibility - Yuan, Yidan; He, Xinyue; He, Quanxing; Jia, Yimeng; Xu, Zhansheng; Li, Man (BMC Psychology, 2023)
With the widespread adoption of smartphones, there has been a notable increase in problematic mobile phone use (PMPU), particularly prevalent among college students. Research suggests that apart from being associated with various problematic behaviors, this excessive mobile phone use might also have an impact on individual personality traits, such as time management disposition (TMD), which plays a significant role in individual motivation and psychological well-being. While previous literature has identified a negative relationship between PMPU and TMD, few studies have delved into the underlying mediating mechanism. Thus, the main aim of this study was to examine the chain mediating effect of sleep quality and cognitive flexibility on the relationship between PMPU and TMD. A total of 921 Chinese college students completed the questionnaire. We collected basic information about the participants and assessed their PMPU, TMD, sleep quality, and cognitive flexibility using the Problematic Mobile Phone Use Scale-10, Adolescence Time Management Disposition Inventory, Pittsburgh Sleep Quality Index scale and Cognitive Flexibility Inventory. The results indicated a significant correlation among all the variables. Moreover, we noted that both sleep quality and cognitive flexibility fully mediated the association between PMPU and TMD. Additionally, a chain mediating effect involving sleep quality and flexibility in this relationship was also identified. We found that sleep quality and cognitive flexibility had a series of multiple mediating effects in the pathway from PMPU to TMD, and both significantly mediated TMD. These findings indicated that impaired cognitive function and sleep quality may contribute to time management difficulties resulting from PMPU, suggesting that problematic behaviors like PMPU can impact one's personality traits. Therefore, interventions should be enhanced to mitigate the adverse effects of PMPU.